Prevalence study of abuse and violence against older women: results of a multi-cultural survey conducted in Austria, Belgium, Finland, Lithuania, and Portugal - Luoma, Minna-Liisa (2011)
Introduction • The study included women aged between 60 and 97 years who were living in private households. The survey asked about violence and abuse in the last 12 months. 2880 women were surveyed across five countries during 2010. • So-called “stranger violence” was ruled out and only perpetrators who were in the women's close circles were considered. • Response rates ranged from 26.1% (Belgium) to 49.1% (Austria). Prevalence of violence and abuse • Overall, 28.1% of older women had experienced some kind of violence or abuse. By country the prevalence rates were as follows: • Portugal 39.4% (postal survey) • Belgium 32.0% (postal survey and face-to-face interviews) • Finland 25.1% (postal survey) • Austria 23.8% (telephone survey (CATI)) • Lithuania 21.8% (face-to-face interviews) • Generally, emotional abuse was the most common form of violence experienced (23.6%) followed by financial abuse (8.8%), violation of rights (6.4%) and neglect (5.4%). Sexual abuse (3.1%) and physical violence (2.5%) were the least reported forms. Perpetrators • In most cases, perpetrators of emotional abuse, financial abuse, sexual abuse and violation of rights were the women's partners or spouses. The exception to this was in relation to neglect, where in most cases older women were abused by their adult children or children-in-law. Intensity of violence • 7.6% of older women had experienced a single form of abuse, but infrequently. • 13.5% had experienced several forms of abuse, but infrequently. • 1.2% had experienced a single form of abuse very often. • 5.8% had experienced multiple forms of abuse very often. Prevalence Study of Abuse and Violence against Older Women – Final Report 8 Risk factors • There were considerable differences between countries with regard to prevalence rates. However, connections between risk factors and abuse and violence were apparent regardless of country. • The likelihood of abuse is lower in higher age groups. • There was a significant association between abuse and violence and reduced physical health, poor mental health, managing poorly with household income, not participating in social activities, living with spouse or partner or with adult children, and loneliness. After the abuse • The most common effects of violence and abuse were tension, anger, hatred and feelings of powerlessness. • Nearly half of the abused women (44.7%) talked with somebody they knew about the most serious incident or reported it to an official agency. In Portugal and Lithuania, however, only a quarter of the abused women talked about the incident with anyone else. • The majority of older women did not talk with anybody else about the abusive incident(s). Mostly women thought the incident was too trivial to report or discuss or considered that nobody could do anything about the situation. Quality of Life • In relation to abuse in overall terms, the findings are unambiguous: older women who had experienced any kind of abuse reported having significantly lower quality of life than older women who had not experienced abuse.